Innovation Strategy for SMES in Shanghai, China - Li, Hao (2016)
This research is mainly dedicated for discussion on influential factors in innovation strategies for SMEs. With the deepening of economic globalization, international market competition intensifies, which brings various innovation methods for SMEs that will continuously upgrade themselves in order to accommodate to changes on the market and alter our production and lifestyle now and in the future. In the course of the rapidly changing environment, exclusive advantages of SMEs could be fully utilized so as to achieve innovation strategies. Stable growth of SMEs could become one vital foundation in national industrial competitiveness within China. Along with varied economic environment, SMEs within China are faced with influences from the institutional environment, coordination and flexibility as well as dynamic core capacity. By studying research questionnaires, it could gather information on the environments during innovation strategies. Furthermore, SMEs adapt more quickly and effectively, thus it makes proper adjustments according to different environments. Therefore, the results of the research is beneficial in taking up the advantageous position within international markets for SMEs.